Zeolite Synthesis Based Silica from Saccharum officinarum L. with Black Stem Using the Hydrothermal Method - Redi, Muhamad; Astuti, Intan Rizki Widya; Ramadhani, Restu Agung; Sopiana, Baiq Nova; Adhya, Farhana Nida ul; Nikmah, Hidayatun; Sudirman, Sudirman; Ningsih, Baiq Nila Sari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Saccharum officinarum L. has a high amount of silica content, which can be used as the main component of zeolite synthesis. Silica was isolated from Saccharum officinarum L. bagasse with NaOH and HCl. This research aims to synthesize zeolite using silica from Saccharum officinarum L. with black stem and alumina from aluminium foil. The Saccharum officinarum L. used in this research was sourced from Lombok Island, West Nusa Tenggara Province, Indonesia. Silica was sourced from Saccharum officinarum L. using the sol-gel method. The silica from the isolation of dregs ash obtained 20 g of silica with a high percentage (yield) of 50%. This study found that 5.29 g of aluminium foil produced 14.29 g of alumina with the addition of 22.50 g of Na2CO3. The zeolite obtained was 3.88 g with a SiO2:Al2O3 ratio of 5:3. From this study, the percent (%) of obtained zeolite was 48.5% from the weight of the silica and alumina produced. The zeolite results synthesized from Saccharum officinarum L. ash were characterized using FTIR. Based on the FTIR results, absorption was found at wave numbers (cm-1) 960, 729, and 668. The zeolite obtained was pure white and had a FTIR spectrum similar to that of Zeolite X from previous research. It can be predicted that the zeolite obtained from this research has been formed. This research is expected to be useful in increasing the effectiveness of the silica extraction process from Saccharum officinarum L. with black stem. Further analysis using XRD and SEM is needed to determine the characteristics of the zeolite produced.